Effect of aging treatment on microstructure and corrosion behavior of a Fe-18Cr-15Mn-0.66N stainless steel. (30th April 2022) - Qiao, Yanxin; Wang, Xinyi; Yang, Lanlan; Wang, Xiaojing; Chen, Jian; Wang, Zhengbin; Zhou, Huiling; Zou, Jiasheng; Wang, Fuhui
Highlights: Effect of isothermal aging on pitting of high-nitrogen stainless steel is studied. Aging time had minor influence on corrosion potential and corrosion current density, but a profound decrease of the pitting potential. The fraction of Cr2 O3 in the passive film decreased with aging time. Abstract: The effect of aging treatment on the microstructure and corrosion behavior of a Fe-18Cr-15Mn-0.66N high-nitrogen stainless steel (HNSS) in 3.5 wt.% NaCl solution was investigated using a series of electrochemical tests, scanning electronic microscopy (SEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). The results showed that the aging treatment led to the precipitation of Cr2 N particles along the grain boundaries and their morphologies changed from dispersive particles to continuous network as the aging time increased up to 60 min. Aging time had minor effects on the corrosion potential and corrosion current density, but resulted in the sharp decrease in the pitting corrosion potential. The passive film behaved as a n-type semiconductor, and the donor density of the passive film increased with the aging time. Meanwhile, the fraction of stable oxide (Cr2 O3 ) in the passive film decreased with the aging time. It demonstrates that the aging treatment deteriorated the protectiveness of the passive film, hence weakened the corrosion resistance of HNSS.